Comparative Effects of Selected Sweeteners on Tooth Surface Demineralization and pH Variation In Vitro - Azores, Yedd Andrea; Mingu, Lee; Supangan, Jeanneth; Testa, Judith Clarisse; Morales, Ruben Jr; Osano, Lady Zarah; Subido, Herminiano Jr; Mercado, Giovani; Mercado, Michelle; Concel, Luke (12th International Scholars Conference 2025, 2026)
Dental caries is a chronic communicable disease of the teeth that has been linked to the metabolism of sugars by the bacteria present in the mouth, particularly Streptococcus mutans. Lactic acid is produced as these two variables interact with each other, together with all the components necessary for demineralization to occur. Part of the purpose of this study is to determine which type of sugar is more capable of producing an acidic environment that could favor the development of dissolution of tooth surface. Sweeteners such as sucrose, fructose, stevia, and xylitol were the selected sweeteners used in this study. Teeth samples were acquired and soaked in different solutions containing sterile water, a colony of Streptococcus mutans, and the aforementioned sweeteners for 10 days. The pH values for each solution and the degree of dissolution formed were gathered and statistically treated using repeated measures ANOVA to determine and compare the mean values. Results showed that fructose obtained the lowest pH value (x̄ = 5.68), while the greatest tooth surface dissolution was seen on the teeth samples soaked in sucrose solutions (x̄ = 1.57 mm). Stevia also produced a high pH value and the third sweetener to produce a significant dissolution. These effects may be caused by the possible ingredients added to the stevia powder bought in the market. Therefore, recommendations include using pure stevia sweeteners and adding more test sets to produce a more favorable data. Proper selection of teeth samples along with the correct choice of tooth surface to be sectioned is also important to minimize measuring areas with already existing incipient lesions.